2013
DOI: 10.1016/j.psychres.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Holistic versus detailed visual processing in body dysmorphic disorder: Testing the inversion, composite and global precedence effects

Abstract: Individuals with Body Dysmorphic Disorder (BDD) are preoccupied with perceived defects in their appearance that are not visible to others. An excessive focus and processing of details has been proposed as a possible mechanism underlying this distorted self-image in BDD. The nature and extent of visuoperceptual abnormalities in BDD however require further investigation; specifically, it remains unclear whether feature-based processing in BDD is a result of a failure of holistic perceptual processes. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
5
27
2
1
Order By: Relevance
“…Our data do not appear to be consistent with the recent findings of Monzani et al (2013). Monzani and colleagues found no evidence for a visual processing bias in individuals with BDD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data do not appear to be consistent with the recent findings of Monzani et al (2013). Monzani and colleagues found no evidence for a visual processing bias in individuals with BDD.…”
Section: Discussioncontrasting
confidence: 99%
“…Monzani, Krebs, Anson, Veale, and Mataix-Cols (2013) fail to see any robust differences in holistic/global versus local processing between BDD patients and controls, across several visual tasks. Significant methodological differences limit the degree to which this result can be compared with previous studies, but nevertheless indicate that more work is needed regarding the specification any contribution of visual processing abnormalities in BDD.…”
Section: Introductionmentioning
confidence: 92%
“…Another study using inverted faces demonstrated that individuals with BDD relative to healthy controls had enhanced ability to recognize inverted faces (Jefferies et al, 2012). Similar results were not found in a more recent study, although shorter presentation times and different stimuli were used (Monzani et al, 2013). Collectively, these studies largely support a local bias and global impairment for faces among BDD individuals and suggest similar deficits may exist for stimuli unrelated to BDD symptoms.…”
Section: Introductionsupporting
confidence: 88%
“…A recent study used a version of the Navon task to examine the global precedence effect in individuals with BDD and healthy controls (Monzani et al, 2013). The global precedence effect refers to the preference and superiority for processing global aspects of a scene at the expense of the local details and is ascertained by comparing consistent letters, in which the global and local letters share identity (e.g., a large H made of smaller Hs) with inconsistent letters, in which the two levels have different identities (e.g., a large S made of small Hs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation